MEMBEDAH HASRAT BELAJAR MAHASISWA IAIDA DI RUANG KULIAH DAN RUANG DINIYAH - GINANJAR PRASTYANTO; Hasyim Iskandar (Jurnal At-Taujih, 2021)
This research focuses on understanding how the desire to learn for IAIDA students who are staying at the Darussalam Islamic Boarding School is, in the lecture hall and also in the diniyah room. Using Lacan's perspective, desire is understood as a person's psychological impulse to perform a certain action, the purpose of which is to fulfill the feeling of deficiency in himself. Desire itself arises from a mirror moment in one's life journey, namely the moment of meeting with another party that makes the person feel lacking in himself. Therefore, we try to trace the life journey of the informants to find each episode of the mirror moment, in order to understand their desire to learn. The results we found were that the students' desire to learn was very complex, and emerged from the complex process of social interaction that took place in the course of their lives.